Growth kinetics and mechanical characterization of boride layers formed on Ti6Al4V - Özger Onur Yiğit; Avcı Şenol (Open Chemistry)
Although Ti6Al4V alloy is used in a wide variety of engineering fields such as automotive, aerospace, chemical, marine, and medical, it has significant disadvantages such as low hardness and wear resistance. The boriding process, which is one of the methods applied to improve the surface properties of the material, is based on the principle of increasing the surface quality of the material by creating a TiB2 and TiB layer on the surface of the material by boron diffusion. Although many methods are used for boriding of Ti6Al4V alloy, the pack boriding method preferred in this study attracts attention because it is a cheap and easy method. This present study focuses on the characterization of the boride layer formed on Ti6Al4V alloy borided at 950, 1,050, and 1,150°C for 5 and 15 h using two different recipes (M-1 and M-2). In addition, the activation energies of boron diffusion calculated using the TiB2 layer thicknesses measured from optical images of all samples, including 10 h borided samples, are included in the article.